10.1177/1056789514562152 (CrossRef Listing of Deleted DOIs, 2015)
IntroductionStatin therapy has been associated with an increased risk of new-onset diabetes mellitus (NODM). This systematic review and meta-analysis compared the risk of NODM between pravastatin and two commonly used statins.MethodsWe searched PubMed/MEDLINE, EMBASE, CENTRAL, and ClinicalTrials.gov from inception to May 23, 2024. Original studies comparing pravastatin with atorvastatin and/or rosuvastatin were included. Risk of bias was assessed using established, study-design-specific tools. Data were pooled using a random-effects model implemented in RevMan version 5.4.1. Statistical heterogeneity was assessed using the I2 statistic.ResultsEighteen studies were included, of which ten contributed to the meta-analysis. The comparison of pravastatin versus atorvastatin (10 studies; N = 95,276 vs 490,905) yielded a pooled risk ratio (RR) of 1.01 (95% CI: 0.77-1.32; I2 = 98%). Pravastatin versus rosuvastatin (9 studies; N = 92,853 vs 114,718) yielded a pooled RR of 1.12 (95% CI: 0.85-1.47; I2 = 96%).ConclusionPravastatin did not demonstrate a lower risk of NODM when compared with atorvastatin or rosuvastatin; nevertheless, further research remains warranted.